Phenomenological Modelling and Fault Diagnosis of Planetary Gear Systems with a Tooth Crack - Liu Zongyao; Mao Shixiang; Wang Yadong; Zhu Wenliang; Liu Baoguo; Liu Shihua (Jixie chuandong)
Fault mechanism is the basis of fault diagnosis, and modelling is an important means to investigate the fault mechanism. The existing research on modelling of planetary gear systems mainly includes the dynamic modelling and the phenomenological modelling. The dynamic modelling is difficult to be established and mainly focuses on dynamic characteristics of a single component. The phenomenological modelling can describe a system from a macroscopic perspective, which is beneficial for the fault diagnosis of planetary gear systems. Root crack is a common fault type in planetary gear systems. In this study, phenomenological modelling of vibration signals of planetary gear systems under normal and cracked conditions are established. Firstly, based on the theory of impact dynamics, the meshing impact force when the gear tooth enters into meshing is calculated, and its effect on the dynamic load factor is simulated. Secondly, phenomenological modelling of vibration signals considering the meshing impact is established, and model responses of planetary gear systems under different health conditions including normal, cracked sun gears and cracked planet gears are obtained. Finally, the model responses are analyzed using the statistical indexes such as root mean square and kurtosis, etc., and the sensitivity of each statistical index in reflecting the crack fault is compared. The comparison results show that the kurtosis can be used as one of the effective indexes to reflect the tooth root crack in planetary gear systems.